ß-HCG serum levels as pre-eclampsia predictor - Castagnini, L (2015)
OBJETIVE: To determine whether the elevation of chorionic gonadotropin beta (ßhCG) in the second trimester of pregnancy is a useful serum marker for predicting preeclampsia. DESIGN: An observational analytic study cases and control type, which employed incident cases. MATERIAL AND METHODS: A pregnant women who were between 14 and 21 weeks gestation, they took a serum sample for measuring the ßhCG. They were followed until the end of pregnancy. The outcome variable was the preeclampsia, which divided the patients in the group of cases (30) and controls (90). RESULTS: The mean serum values of ßhCG was 086.67 ± 76 584.65 92 mIU / mL in 69 cases and 55 929.25 ± 796.67 mIU / mL in the control group (p = 0, 15). The risk of having the b-hCG over 153 000 mIU / mL and 204 000 mIU / mL in patients with preeclampsia was 3.72 (1.26 -11.05) and 6.77 (1,17- 39,07), respectively. Patients with severe preeclampsia had a risk 8.2 (1.9 to 36.8) times more likely to have hormone levels over 153 000 mIU / mL that they had no disease. CONCLUSION: ßhCG could be used as a serum marker for predicting preeclampsia.